Die Konusspinne Cyclosa conica (Araneae: Araneidae) ist die Europäische Spinne des Jahres 2016 - Hörweg, Christoph (Arachnologische Mitteilungen, 2016)

(untitled)
The European spider of the year 2016, Cyclosa conica (Pallas, 1772), is presented. Its appearance and characteristics (e.g., ecology, habitat, phenology) are briefly described. The modality of the voting is given as well as numerous links to the supporting societies and to distribution maps.